A case of type 2 amiodarone-induced thyrotoxicosis - O. O. Soloviuk; R. L. Kulynych; O. A. Soloviuk (Zaporožskij Medicinskij Žurnal)
Iodine-induced thyrotoxicosis (IIT) is an abnormal function of the thyroid gland towards increasing caused by excessive iodine intakes of the body. The main reasons for the development of IIT are effects of increased amounts of iodine in people with long-standing iodine deficiency, medical procedures with exposure to radiographic iodinated contrast media as well as long-term treatment with iodine-containing drugs, primarily amiodarone.